Evaluation of the pattern dimensions of cast-metal posts in uniradicular teeth - Rafael de Assunção Vital; Jessica Silva Ribeiro; Sicknan Soares da Rocha
Introduction Accurate dimensions of cast-metal posts are relevant to the survival of dental prostheses. Objective The aim of this study was to verify if the dimensions of cast-metal posts accord with ideal clinical criteria. Material and method For the evaluation, 285 periapical radiographs, from a total of 80 teeth, were taken from the charts of patients that attended the clinics at the Dental School of the Federal University of Goiás, from March 2008 to October 2012. Only periapical radiographs of single-rooted teeth with post and core were included in the study. The radiographic evaluation was conducted with the assistance of a magnifying glass and a view box, in a room with low luminosity. The dimensions of the post and core were established with the help of a digital caliper, and the following measurements were considered: a) LR (Length Remnant); b) LP (Length Post); c) BS (Bone Support); d) DR (Diameter Root); e) DP (mesiodistal diameter post). The post and core were classified as acceptable or deficient by reference values with a margin of error of 0.2 mm. For descriptive analysis, the data were cataloged using SPSS software (version 17.0). Result With regard to the length of the post and core, only 26.25% and 43.75% of the post and core were classified as acceptable according to the two-thirds rule and fulcrum dental rule, respectively. With regard to the mesiodistal diameter of the post and core, 55% were classified as acceptable. Conclusion Within the limits of this study, it can be concluded that the cast-metal posts evaluated do not accord with the ideal clinical criteria.